2016
DOI: 10.1111/cdev.12482
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Placental NR3C1: Mechanism Underlying Prenatal Programming of Infant Neurobehavior by Maternal Smoking?

Abstract: Epigenetic regulation of the placental glucocorticoid receptor gene (NR3C1) was investigated as a mechanism underlying links between maternal smoking during pregnancy (MSDP) and infant neurobehavior in 45 mother-infant pairs (49% MSDP-exposed; 52% minorities; ages 18-35). The NICU Network Neurobehavioral Scale was administered 7 times over the first postnatal month; methylation of placental NR3C1 was assessed via bisulfite pyrosequencing. Increased placental NR3C1 methylation was associated with increased infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 53 publications
(104 reference statements)
1
43
0
Order By: Relevance
“…R. Stroud, R. L. Paster, M. S. Goodwin, et al, 2009). We found decreased ability to self-regulate reactions to environmental stimuli (self-regulation/need for external handling), decreased ability to attend to stimuli (attention), and altered motor activity (lethargy) in MSDP-exposed vs. comparison infants (Law et al, 2003; Stroud, Papandonatos, Salisbury, et al, 2016; Stroud, Paster, Papandonatos, et al, 2009). Additional studies have found increased odds of MSDP exposure in NNNS profiles characterized by altered arousal, activity, muscle tone, attention, and signs of stress (Appleton et al, 2016; Liu et al, 2010).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…R. Stroud, R. L. Paster, M. S. Goodwin, et al, 2009). We found decreased ability to self-regulate reactions to environmental stimuli (self-regulation/need for external handling), decreased ability to attend to stimuli (attention), and altered motor activity (lethargy) in MSDP-exposed vs. comparison infants (Law et al, 2003; Stroud, Papandonatos, Salisbury, et al, 2016; Stroud, Paster, Papandonatos, et al, 2009). Additional studies have found increased odds of MSDP exposure in NNNS profiles characterized by altered arousal, activity, muscle tone, attention, and signs of stress (Appleton et al, 2016; Liu et al, 2010).…”
mentioning
confidence: 82%
“…Our group conducted some of the first studies of associations between MSDP and infant neurobehavior using the NICU Network Neurobehavioral Scale (NNNS, behavior exam designed to be sensitive to subtle deficits in substance-exposed infants) and rigorous measures of MSDP including prospective measures of timing, quantity, and biomarkers of exposure (Law et al, 2003; L. Stroud et al, 2009; Stroud, Papandonatos, Rodriguez, et al, 2014; Stroud, Papandonatos, Salisbury, et al, 2016; L. R. Stroud, R. L. Paster, M. S. Goodwin, et al, 2009).…”
mentioning
confidence: 99%
“…39 Alternatively, epigenetic effects may explain these effects of maternal smoking; for example, PTE seems to alter DNA methylation which may cause or signal a risk for smoking 11 and other adverse outcomes. 40 Other hereditary effects not included in this study, such as behavioral disinhibition or other personality traits, 41 could also explain these findings.…”
Section: Discussionmentioning
confidence: 85%
“…A recent study showed that maternal smoking during pregnancy induced hypomethylation at CpG3 and CpG4 in total 13 CpG of the placental NR3C1 gene, which has shown associations with newborn behavior [160]. Prenatal smoke exposure is known to result in a persistent effect on DNA methylation levels in adult peripheral blood granulocytes, as measured by repetitive element satellite 2 (Sat2) [161].…”
Section: Epigenetic Alterations By Environmental Toxicantsmentioning
confidence: 99%